Optimal estate taxation: More (about) heterogeneity across dynasties - Philipp Krug (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2022)
Standard models on optimal estate taxation do not allow for intergenerational transmission of bequest motives. However, correlation in bequest motives may exist due to genetic and cultural transmission of preferences or indirect reciprocity. I introduce such intergenerational correlation to a simple model with heterogeneously altruistic parents. I derive two insights for optimal linear estate taxation under a Utilitarian welfare measure. First, this correlation implies a higher optimal estate tax rate. Second, estate tax rates should be higher for those parents who inherited themselves.
Keywords: H21; H24; D64; 330; estate taxation; inheritance taxation; indirect reciprocity; intergenerational preference transmission